A bout of voluntary running enhances context conditioned fear, its extinction, and its reconsolidation - Siette, Joyce; Reichelt, Amy C.; Westbrook, R. Frederick (Learning & memory (Cold Spring Harbor, N.Y.), 2014)
Three experiments used rats to examine the effect of a single bout of voluntary activity (wheel running) on the acquisition, extinction, and reconsolidation of context conditioned fear. In Experiment 1, rats provided with access to a wheel for 3 h immediately before or after a shocked exposure to a context froze more when tested in that context than rats provided with access to the wheels 6 h after the shocked exposure or rats not provided with access to the wheels. In Experiment 2, rats provided with access to the wheels immediately before or after a nonshocked exposure to the conditioned context froze less when tested in that context than rats provided with access to the wheels 6 h after the nonshocked exposure or rats not provided with access to the wheels. In Experiment 3, rats provided with access to wheels immediately after an extended nonshocked exposure to the conditioned context again froze less, whereas rats provided with access to the wheels after a brief nonshocked exposure froze more on the subsequent test than sedentary controls. These results show that a single bout of running can enhance acquisition, extinction, and reconsolidation of context conditioned fear.